2016
DOI: 10.15376/biores.11.2.4281-4294
|View full text |Cite
|
Sign up to set email alerts
|

Regenerated Lignocellulose Beads Prepared with Wheat Straw

Abstract: The conversion of lignocellulosic biomass into fine chemicals and polymers has been gaining attention recently. Regenerated lignocellulose beads (RLBs) were prepared by an emulsification/precipitation technique, using wheat straw as a raw material and [Bmim]Cl as a solvent. The morphology and properties of the obtained beads were characterized. The RLBs were perfectly spherical, with a porous microstructure, and had a huge specific surface area (142.4 m 2 /g). Their components were similar to that of wheat str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…When comparing the components between raw sugarcane bagasse and LCB, it can be found that cellulose and hemicellulose contents slightly increased after dissolution-regeneration process, whereas lignin decreased. This phenomenon is consistent with the findings reported in the previous studies (Zhang et al 2016). It should be noted that the ash content was relatively high, which may have resulted from the insufficient combustion of the acid insoluble matter in the test.…”
Section: Basic Physicochemical Propertiessupporting
confidence: 94%
See 1 more Smart Citation
“…When comparing the components between raw sugarcane bagasse and LCB, it can be found that cellulose and hemicellulose contents slightly increased after dissolution-regeneration process, whereas lignin decreased. This phenomenon is consistent with the findings reported in the previous studies (Zhang et al 2016). It should be noted that the ash content was relatively high, which may have resulted from the insufficient combustion of the acid insoluble matter in the test.…”
Section: Basic Physicochemical Propertiessupporting
confidence: 94%
“…According to a general classification, pores in material are distinguished based on their diameter as micropores (< 2 nm), mesopores (2 to50 nm), and macropores (> 50 nm). The LCB in the present work had similar density (g/cm 3 ) and porosity (%) with a reported wheat straw-based lignocellulose bead, but much larger pore diameter and volume (Zhang et al 2016). It should be noted that LCB-AE had a lower total intrusion volume and pore area than LCB, implying that chemical modification may block the pores and reduce the pore area and volume.…”
Section: Pore Structures Characterization By Mipsupporting
confidence: 67%
“…The cost of energy increased in the 1950s, and as a result many countries chose to use the incineration of agricultural biomass to generate household energy and heating (Yui et al 2018;Nesterovic et al 2021). The atmospheric pollution generated via incineration, e.g., the open-air combustion of straw, has become a major environmental problem (Zhang et al 2016;Wu et al 2020;Guo and Zhao 2021;Huang et al 2021). Particulate matter, including PM2.5 and PM10, emitted from such incineration increases global warming and reduces air quality, which leads to the premature death of organisms among other effects (Beig et al 2021;Liu et al 2021;Manojkumar and Srimuruganandam 2021).…”
Section: Conversion Of Agricultural Biomass Into An Energy Source Inc...mentioning
confidence: 99%